A Low-Sidelobe-Level Variable Inclination Continuous Transverse Stub Antenna with a Nonlinear Slow-Wave Structure - Kexin Wang; Xue Lei; Jun Gao; Tianpeng Li; Siyu Tian; Mingyang Zhao (International Journal of Antennas and Propagation)
The sidelobe level (SLL) is an essential performance factor for satellite communication antennas. A low-SLL design can effectively suppress adjacent satellite interference. A low-SLL design method for a variable inclination continuous transverse stub (VICTS) antenna is proposed in this paper. The VICTS antenna is composed of three rotatable parts: a feeding plate, a radiation plate, and a polarization plate. The radiation plate comprises two groups of stubs with different radiation ratios. Combined with the nonlinear slow-wave structure attached to the feeding plate, the radiation ratio of the unit can be adjusted. The aperture field of the VICTS antenna using this method can be tapered in order to suppress the SLL. To verify the effectiveness of this method, the antenna prototype is fabricated and measured in a microwave anechoic chamber. The simulation and the measurement are in good agreement. The reflection coefficient of the antenna is kept below −15 dB and between 13.75 GHz and 14.5 GHz. When the radiation plate and the feeding plate rotate relative to each other, the pattern beam can be scanned from 5° to 70°. In the scanning range, the typical SLL can reach −18 dB.